Phylogenetic relationship of terubok fishes (Genus Tenualosa: clupeidae) inferred from sequencing of ytochrome B mitochondrial DNA fragment - Nadiah, Binti Halim (Faculty of Resource Science and Technology, 2012)
This study examines the phylogenetic relationship among three different species of Tenualosa toli, Tenualosa macrura and Tenualosa ilisha. A total of ten T toli, two T macrura and three T ilisha nucleotide sequences were analysed. The sequences of Tenualosa ilisha obtained from Genbank was used in this study. Phylogenetic results supports the monophyletic status between the three terubok with high genetic distances (13.943-16.033%) between them. The nucleotide sequences were subjected to phylogenetic analyses by using the neighbor-joining, maximum parsimony, and Bayesian analyses produced similarity tree topologies with only the maximum likelihood tree was slightly different on the position of T ilisha. Overall, this study has managed to provide useful informations on the phylogenetic status of terubok in Sarawak.